Determinants of households’ intention to practise solid waste segregation-at-source in Selangor, Malaysia - Cheng, Kai Wah (2020)
Municipal solid waste management is the most critical environmental problem in Malaysia. The main purpose of this research was to explore the current scenarios of intention to practise solid waste segregation-at-source among households in Selangor; to evaluate the levels of attitude, subjective norms, environmental concerns, environmental knowledge, and intention to practise solid waste segregation-at-source; to investigate the relationships between households’ attitude, descriptive norm, and injunctive norm with the intention to practise solid waste segregation-at-source; as well as to ascertain the mediating effect of environmental concerns and the moderating effect of environmental knowledge between households’ attitude, descriptive norm, and injunctive norm with the intention to practise solid waste segregation-at-source. A total of 400 residents living in the townships of the nine districts of Selangor were selected via a multistage sampling method. A self-administrated bilingual questionnaire was used to collect the quantified research data. The measurements were adapted and adopted from different sources to examine the key variables in this research. The results revealed that descriptive norm [p = 0.038 (p ≤ 0.05), r = 0.104] and injunctive norm [p = 0.000 (p ≤ 0.001), r = 0.317] have positive relationships with the intention to practise solid waste segregation-at-source. However, the results also revealed that there was an insignificant relationship between attitude [p = 0.139 (p > 0.05), r = 0.074] and the intention to practise solid waste segregation-at-source. Hence, it was excluded from the further mediation and moderation test throughout the research. In terms of mediation test, the egoistic concern [p = 0.001 (p ≤ 0.001), t = 3.182] as well as the altruistic concern [p = 0.000 (p ≤ 0.001), t = 4.462] were found to mediate the significant relationship between injunctive norm and intention to practise solid waste segregation-at-source. From the perspectives of moderation test, the results postulated that environmental knowledge did not moderate the relationships between descriptive norm [p = 0.511 (p > 0.05), t = 0.658] and injunctive norm [p = 0.519 (p > 0.05), t = 0.645] with the intention to practise solid waste segregation-at-source. The findings provide an insight for the Malaysian citizens, governmental bodies, non-governmental organisations, and voluntary bodies to strengthen the sense of responsibility to maintain the cleanliness of the environment. The current research data, in particular, is able to provide a direction to the Malaysian governmental bodies, including National Solid Waste Management Department, Solid Waste Management and Public Cleansing Corporation, Malaysian Ministry of Energy, Science, Technology, Environment and Climate Change as well as Malaysian Ministry of Housing and Local Government in their future policy planning and implementation. Instead of using the ordinary self-administrative bilingual questionnaire, future research is recommended innovating different mode of instrumentation to evaluate the respondents' behavioural changes for creating a comprehensive understanding of the solid waste segregation-at-source policy among Malaysian citizens.